UNIT 10F.1 Laboratory Maintenance of Nocardia Species. Issue 1 (3rd November 2015) - Dhakal, Dipesh; Sohng, Jae Kyung
Abstract : Nocardia spp. are aerobic, Gram‐positive, catalase‐positive, non‐motile actinomycetes. Various species of the genus Nocardia have attracted attention due to their detrimental effects on human health. Recent discoveries, however, have exposed their importance as producers of bioactive compounds and degraders of complex organic compounds, as well as their involvement in biotransformation into valuable products. This unit includes general protocols for the laboratory maintenance of Nocardia spp., including growth in liquid medium, growth on solid agar, and long‐term storage. Nocardia sp. CS682 (KCTC11297BP), isolated from soil collected in Jeonnam, Korea, is used as a prototype for explaining the considerations for efficient laboratory maintenance of Nocardia spp. © 2015 by John Wiley & Sons, Inc.